IMPLEMENTATION OF SELF-REGULATED LEARNING ON JUNIOR HIGH SCHOOL STUDENT OF LOW SOCIOECONOMIC STATUS - Fatin Rohmah Wahidah; Farida Kurniawati (Psychosophia: Journal of Psychology, Religion, and Humanity, 2020)
The purpose of this study was to determine the application of self-regulated learning interventions to increase learning motivation and learning abilities in junior high school students who come from families with low socioeconomic levels. The intervention was given for five sessions through psychoeducation and assignments. The subject of this study is a male, 15 years old. This study uses a qualitative method with a case study approach. Data analysis using triangulation techniques. The results of the analysis of observations, interviews, and assignment documents show that there are differences before and after the subject was given intervention. In general, self-regulated learning intervention has a positive impact on learning motivation and learning abilities of the subject. Several factors that support and inhibit intervention were explained. Some suggestions are given to develop the further intervention.